Monocyte Transmodulation: The Next Novel Therapeutic Approach in Overcoming Ischemic Stroke? - Park, Joohyun; Chang, Ji Young; Kim, Jong Youl; Lee, Jong Eun (Frontiers in Neurology, 2020)
The immune response following neuroinflammation is a vital element of ischemic stroke pathophysiology. After the onset of ischemic stroke, a specialized vasculature system that effectively protects central nervous system tissues from the invasion of blood cells and other macromolecules is broken down within minutes, thereby triggering the inflammation cascade, including the infiltration of peripheral blood leukocytes. In this series of processes, blood-derived monocytes have a significant effect on the outcome of ischemic stroke through neuroinflammatory responses. As neuroinflammation is a necessary and pivotal component of the reparative process after ischemic stroke, understanding the role of infiltrating monocytes in the modulation of inflammatory responses may offer a great opportunity to explore new therapies for ischemic stroke. In this review, we discuss and highlight the function and involvement of monocytes in the brain after ischemic injury as well as their impact on tissue damage and repair.